HER+ work package 2: Bundling Socio-technical Innovations (STIBs) for women’s resilience and empowerment in Africa and Asia - Puskur, Ranjitha; Nchanji, Eileen; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Chadha, Deepali; Mukhopadhyay, Prama; Gartaula, Hom; Mapedza, Everisto D. (2023)
Summarized activities of how socio-technical bundles have been integrated and taken up by partners in the learning labs in Kenya, Ethiopia and India